Имя Чехова и рассказ И. Бунина «Господин из Сан-Франциско» - Богданова, Ольга Владимировна; Bogdanova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статье переосмысляется традиционная идейная составляющая рассказа и предлагается новый взгляд на классический текст русской литературы. Имя А. П. Чехова напрямую связывается с историей создания рассказа и обстоятельствами, породившими философские размышления Бунина. Предлагается перейти от негативной аксиологии образа господина из Сан-Франциско, отказаться от социологической составляющей его оценочности, взглянуть на характер персонажа шире и увидеть за ним образ общечеловеческий, судьбу каждого человека – господина ли, слуги, писателя или художника, самого Бунина или Чехова.The article «The Name Chekhov and I. Bunin’s story “The Gentleman from San Francisco”» by O. V. Bogdanova contents rethinking traditional ideological component of the story and offers a new view on the classic text of Russian literature. The name of A. P. Chekhov directly associated with the history of the story and the circumstances that gave rise to Bunin philosophical reflections. The author proposes to move from a negative axiology of the image of the gentleman from San Francisco, to abandon the sociological component of his evaluation, to look wider at the nature of the character and to see into it every single person − a gentleman, a servant, a writer or an artist, Bunin or even Chekhov.
The Chekhov’s Name and the Bunin’s Story «The Gentleman from San Franciscо»
Keywords: русская литература начала ХХ века; А. П. Чехов; И. А. Бунин; проза; традиция; рассказ; идея; символ; деталь; элементы биографизма; Russian literature of the early twentieth century; A. P. Chekhov; I. A. Bunin; literature; tradition; story; idea; symbol; detail; biographism items